2006
DOI: 10.1364/ao.45.004554
|View full text |Cite
|
Sign up to set email alerts
|

Pixelated mask spatial carrier phase shifting interferometry algorithms and associated errors

Abstract: In both temporal and spatial carrier phase shifting interferometry, the primary source of phase calculation error results from an error in the relative phase shift between sample points. In spatial carrier phase shifting interferometry, this phase shifting error is caused directly by the wavefront under test and is unavoidable. In order to minimize the phase shifting error, a pixelated spatial carrier phase shifting technique has been developed by 4D technologies. This new technique allows for the grouping of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…It operates at a wavelength of 511nm or 660nm and utilizes a Linnik interference objective at a magnification of 20X NA 0.45 and 50X NA 0.8 with additional magnification obtained via a flip-in 2X field of view (FOV) lens. The camera is an Illunis XMV-2020 with a Moxtek pixelated phase mask to enable spatial phase measurement with short exposures (<1ms) at frame rates as high as 15fps to freeze motion while being insensitive to vibration [3,4]. For the examples in this paper, objects are viewed in double pass on a reflective surface as shown in Figure 1.…”
mentioning
confidence: 99%
“…It operates at a wavelength of 511nm or 660nm and utilizes a Linnik interference objective at a magnification of 20X NA 0.45 and 50X NA 0.8 with additional magnification obtained via a flip-in 2X field of view (FOV) lens. The camera is an Illunis XMV-2020 with a Moxtek pixelated phase mask to enable spatial phase measurement with short exposures (<1ms) at frame rates as high as 15fps to freeze motion while being insensitive to vibration [3,4]. For the examples in this paper, objects are viewed in double pass on a reflective surface as shown in Figure 1.…”
mentioning
confidence: 99%
“…Then, several single-shot inline phase-shifting techniques [8-10] were proposed to achieve instantaneous measurement without the unwanted images. However, in these techniques, either an array of optical devices [8], a grating [9], or the measurement of the complex amplitude of the reference wave [10] is required, and the optical implementations of each technique are complicated.Recently, SCPS interferometry [11,12] has been applied to digital holography to achieve instantaneous measurement using a simple setup [13][14][15][16]. In this technique, however, it has been reported that the phase-shift error is inherently occurred by the phase shift of the object wave against that of the reference wave [12].…”
mentioning
confidence: 99%
“…Recently, SCPS interferometry [11,12] has been applied to digital holography to achieve instantaneous measurement using a simple setup [13][14][15][16]. In this technique, however, it has been reported that the phase-shift error is inherently occurred by the phase shift of the object wave against that of the reference wave [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations